Building Gender-Responsive Education through Hybrid Indigenous Institutions: Lessons from An Island Community in Indonesia - Simona Christina Henderika Litaay; Afdhal Afdhal; Nathalia Debby Makaruku (Universitas Pattimura, 2026)
Gender-responsive education has predominantly been examined through the lens of state policies and formal educational institutions, while limited attention has been given to the role of indigenous community governance in shaping educational equity. This study develops a conceptual understanding of how hybrid indigenous institutions foster gender-responsive education within an island community in Eastern Indonesia. Adopting a theory-building qualitative case study, the research was conducted in Negeri Mamala, where the Three-Stone Indigenous Institutions continue to organize community life. Data were collected through in-depth interviews, participant observation, focus group discussions, and document analysis involving local government officials, customary and religious leaders, school principals, teachers, parents, youth, and young women. The findings reveal that gender-responsive education emerges not primarily through formal policy implementation but through continuous social negotiation among interconnected local institutions. The Three-Stone Indigenous Institutions function as a collaborative governance mechanism that strengthens social legitimacy for girls’ education, while the cultural value of badraheng has been reinterpreted from a traditional norm into a collective resource supporting educational participation and women’s economic empowerment. Nevertheless, patriarchal gender norms, unequal access to entrepreneurship education, and limited family engagement remain significant constraints. This study proposes the Hybrid Indigenous Educational Governance model, demonstrating that gender-responsive education is produced through dynamic interactions among customary institutions, local government, religious organizations, families, schools, and indigenous cultural values, thereby extending existing theories of gender-responsive education beyond formal institutional frameworks toward community-based educational governance.